Pharmacology - Ahrens, Franklin A. (Baltimore : Williams & Wilkins, 1996)
A system for learning and review. Basic and clinical veterinary sciences are outlined in a format that enables to master large amounts of information in a limited amount of time. This book in the "National Veterinary Medical Series" helps prepare for the National Boards and the Clinical Competency Test and is a resource for problem-based learning.
1. Principles of Drug Absorption, Disposition, and Action. p. 1. 2. Drugs Affecting Peripheral Neurohumoral Transmission. p. 21. 3. Autacoids and Their Antagonists. p. 45. 4. Drugs Acting on the Central Nervous System. p. 61. 5. Anesthetics. p. 85. 6. Drugs Acting on the Cardiovascular System. p. 111. 7. Diuretics. p. 139. 8. Endocrine Pharmacology. p. 151. 9. Nonnarcotic Analgesics and Nonsteroidal Anti-inflammatory Drugs. p. 173. 10. Drugs Acting on the Gastrointestinal Tract. p. 189. 11. Antimicrobial Drugs. p. 207. 12. Antineoplastic Drugs. p. 229. 13. Antiparasitic Agents. p. 243. 14. Drug Interactions. p. 265. 15. Treatment of Poisoning. p. 271. Comprehensive Exam. p. 283. Index. p. 301.
Includes index.
Keywords: Veterinary pharmacology -- Outlines, syllabi, etc; Veterinary pharmacology -- Examinations, questions, etc; Veterinary medicine -- Use of -- Drugs